Effect of Immigration on Uganda's Labour Market: A Case Study of Northern Division Kabale Municipality. - Akampurira, Jonath (Kabale University, 2025)
The phenomenon of immigration holds significant implications for labor markets and local communities, particularly in regions experiencing rapid demographic shifts. This research report investigates "The Effect of Immigration on Uganda's Labor Market: A Case Study of Northern Division, Kabale Municipality." Employing a mixed-methods approach, the research integrated quantitative surveys and qualitative interviews to capture diverse perspectives and insights. The methodology encompasses rigorous sampling procedures, data collection methods, and analytical techniques to ensure the validity and reliability of findings. Ethical considerations, including informed consent and confidentiality, were prioritized throughout the research process. Despite potential limitations, the study seeks valuable insights into the complex interplay between immigration and labor market dynamics, informing evidence-based policies and interventions to address the challenges and opportunities posed by immigration in Uganda's local communities. The findings reveal that immigration contributes positively to cultural diversity and economic growth, bringing valuable skills and expertise to the local labor market. However, challenges such as job competition, wage suppression, social tensions, and exploitation of immigrant workers were also identified. The study concludes that comprehensive and balanced policies are needed to maximize the benefits of immigration while addressing associated challenges. Recommendations include developing inclusive integration.